Model Stock Price Valuation Approach Based Company Intrinsic Value In the National Logistics System Development (Sislognas ) - Andi Desfiandi; Abshor Marantika (Proceeding International Conference on Information Technology and Business, 2016)
Valuation is the process of determining what a reasonable price for a stock value approach used is one of determining the intrinsic value of securities, the value of the securities should be based on facts. The output of this research is Products in the form of design models stock price valuation approach based on intrinsic value. Explanatory research which explains the causal relationship and correlation between variables through hypothesis testing. Explanatory research aims to clarify the relationship between the variables through hypothesis testing based on field data. Sampling with the specified criteria, namely: the company has a market capitalization terbersar, a company listed on the LQ-45 August 2013 - January 2014, the company paid dividends in 2013 and the company does not undertake stock split The documentation can be done by collecting data by retrieving data from the record, and the corresponding report to the problems examined, which is where the work was related to the object that the stock price valuation. The stage of collecting data in the field by Moleong (2000: 85-103), can be divided into three, namely; pre-court stage, the stage of field work and data analysis stage. Key word: Stock Price, Intrinsic Value